PENGARUH GAYA KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI KARYAWAN UKM DI WILAYAH DEPOK JAWA BARAT - Dede Suryanto; Wulan Prihatiningsih (Jurnal Vokasi Indonesia, 2016)
Organizational commitment is a psychological state that characterizes employee relationship with theorganization. It has implication for the decision to continue membership in the organization. Employee withhigh commitment is a valuable asset in operating the company in order to maintain Company’s sustainability.This research proposes that organizational commitment is influenced by leadership style. The hypothesis istested using data obtained from 60 respondents who work in Small and Medium enterprises in Depok. Theresults shows that transformational leadership style affects positively on affective commitment but it doesn’taffect normative commitment. Besides that, transactional leadership style doesn’t affect continuancecommitment, while passive / avoidant leadership style does not affect affective commitment.Keyword : tranformasional, transaksional, passive/avoidant, komitmen afektif, komiitmen normatif,komitmen keberlanjutan.